Short-term managerial contracts and cartels - Martijn A. Han (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2012)
This paper shows how a series of commonly observed short-term CEO employment contracts can improve cartel stability compared to a long-term employment contract. When a manager's short-term appointment is renewed if and only if the firm hits a certain profit target, then (i) defection from collusion results in superior firm performance, thus reducing the chance of being fired, while (ii) future punishment results in inferior firm performance, thus increasing the chance of being fired in the future. The introduction of this re-employment tradeoff intertwines with the usual monetary tradeoff and can improve cartel stability. Studying the impact of fixed versus variable salary components, I find that fixed components can facilitate collusion with a short-term contract, while not affecting cartel stability with a long-term contract. Moreover, an extension of the model shows that short-term, renewable contracts can be a source of cyclical collusive pricing. Finally, interpreting the results in light of firm financing suggests that debt-financed firms can form more-stable cartels than equity-financed firms.
Keywords: L13; L22; L41; 330; cartels; collusion; managerial contracts; price wars; Kartell; Gleichgewichtsstabilität; Führungskräfte; Arbeitsvertrag; Theorie